Do visual word segmentation cues improve reading performance in Chinese reading？. Issue 8 (3rd August 2019) - Ma, Guojie; Li, Danxin; Zhuang, Xiangling
Abstract: It is controversial whether providing visual word segmentation cues can improve Chinese reading performance. This study investigated this topic by examining how visual word segmentation cues such as grey highlighting, red colour and interword spacing influence global sentence reading and local word recognition during reading Chinese text in three experiments. The results showed that interword spacing could facilitate local word recognition but could not increase reading speed. In contrast, grey highlighting and red colour could improve neither local word recognition nor global sentence reading performance. Instead, these cues increased the number of fixations and saccades, resulting in slower reading speed. These results suggest that even red colour is not a practically visual cue for Chinese word segmentation and the corresponding mechanisms were discussed. Practitioner Summary: We studied how visual cues such as grey highlighting, red colour and interword spacing influenced Chinese reading performance. Our data showed that even the red colour was not an efficient cue for Chinese word segmentation. The corresponding mechanisms and future direction were discussed regarding how to improve Chinese reading performance.